MTH245 - Math for Bio, Mgmt, Soc Science - OER (Public) Version - Mary Campbell (2017)
A survey course of discrete mathematics for non-physical science majors. Topics include systems of inequalities, linear programming, probability and probability distributions, and an introduction to descriptive statistics. The course emphasizes problem solving through the use of computer spreadsheets.